If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8c = -10c + -8 Reorder the terms: -8c = -8 + -10c Solving -8c = -8 + -10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '10c' to each side of the equation. -8c + 10c = -8 + -10c + 10c Combine like terms: -8c + 10c = 2c 2c = -8 + -10c + 10c Combine like terms: -10c + 10c = 0 2c = -8 + 0 2c = -8 Divide each side by '2'. c = -4 Simplifying c = -4
| 3r+7x+1=2(5x+1) | | 2+8q=8+9q | | 6x(x+1)=20-x | | 16/8=x/12 | | R-12=28 | | 0.876n=0.625n+4 | | 8-4d=-2d-10 | | 8=log(x/10^-12) | | R-12=12 | | 4/36=2/x | | 1.2(2.5x-2.6y)-3.5(2.0x+1.5y)= | | 5/12=x/5 | | y/9-7= | | 3-k=2k | | 1/3(3.14(3)^2)10 | | 1/3=log8(5x-1) | | -2x+5=15+(-2x)-10 | | 3x+4y=4.40 | | -5m=-6m+6 | | -3+4n=n | | 7=100-3b | | 13r=-15/7 | | -17+10x=8x+13 | | x^2+11x-126=0 | | 6y-3(4/3y-2) | | 1/7x | | un=-2*0.5n | | 34+p=51 | | 3/5=x/21 | | 4v-2+2(6v+8)=-2(v+1) | | 7/9=x/54 | | -3w-1/2=7/5w-7/5 |